The Psylloidea (Hemiptera) of Israel - Spodek, Malkie; Burckhardt, Daniel; Freidberg, Amnon (Zootaxa, 2017)
The psyllids or jumping plant-lice of Israel are reviewed from literature records and collected insect material. Eighteen species are reported from Israel for the first time, bringing the total to 94 species from 35 genera, in five families. Three species are described as new: Caillardia springatei Spodek & Burckhardt, Craspedolepta merzi Spodek & Burckhardt and Eremopsylloides vicinus Spodek & Burckhardt, and one new combination is proposed: Crastina heslopharrisoni (Samy, 1972), comb. nov. from Craspedolepta. Six additional unidentified species are recorded from the genera Bactericera (2 species), Cacopsylla, Craspedolepta, Eryngiofaga and Pachypsylloides. We list new taxa for Israel, update the taxonomy and indicate the known geographic distribution for each species. Host plants and economically important psyllids are discussed. A key to adult psyllids is provided.